2022
DOI: 10.1002/ijgo.14472
|View full text |Cite
|
Sign up to set email alerts
|

Quality of maternal and newborn care around the time of childbirth for migrant versus nonmigrant women during the COVID‐19 pandemic: Results of the IMAgiNE EURO study in 11 countries of the WHO European region

Abstract: Objective: To describe the perception of quality of maternal and newborn care (QMNC) around the time of childbirth among migrant and nonmigrant women in Europe. Methods: Women who gave birth at a health facility in 11 countries of the WHO European Region from March 2020 to July 2021 were invited to answer an online questionnaire including demographics and childbirth experience. Data were analyzed and compared for 1781 migrant and 20 653 nonmigrant women.Results: Migrant women who experienced labor perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The IMAgiNE EURO surveys show high levels of medicalization throughout Europe, especially cesarean, instrumental births, and application of fundal pressure 1–10 . This is also coupled with lack of informed consent, lack of support for initiation and continuation of breastfeeding, and lack of respect and dignity for birthing women.…”
Section: White Ribbon Alliance (Wra)mentioning
confidence: 99%
See 2 more Smart Citations
“…The IMAgiNE EURO surveys show high levels of medicalization throughout Europe, especially cesarean, instrumental births, and application of fundal pressure 1–10 . This is also coupled with lack of informed consent, lack of support for initiation and continuation of breastfeeding, and lack of respect and dignity for birthing women.…”
Section: White Ribbon Alliance (Wra)mentioning
confidence: 99%
“…This is also coupled with lack of informed consent, lack of support for initiation and continuation of breastfeeding, and lack of respect and dignity for birthing women. The results were even worse for women who were not from the majority population—young, immigrant, or from linguistic minorities 9,10 . With the increase in medicalization, including cesarean and instrumental vaginal birth (IVB), women reported feeling that they were treated with less dignity and respect 1 .…”
Section: White Ribbon Alliance (Wra)mentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent review of immigrant women’s experiences with maternity care in Europe highlighted the challenges around navigating new health systems, language barriers, and quality of care 13. Further, a multi-country survey from 11 countries also in Europe found that immigrant women reported more barriers in accessing facilities, less timely care, less comfortable care, and more negative experiences, including more separation from infants, fewer offers for pain relief, and more requests for informal payments, than non-immigrant women 14…”
Section: Introductionmentioning
confidence: 99%
“… 13 Further, a multi-country survey from 11 countries also in Europe found that immigrant women reported more barriers in accessing facilities, less timely care, less comfortable care, and more negative experiences, including more separation from infants, fewer offers for pain relief, and more requests for informal payments, than non-immigrant women. 14 …”
Section: Introductionmentioning
confidence: 99%